Along-Strike Variation in Accretion, Non-accretion, and Subduction Erosion Recorded in Rocks of the Jurassic-Neogene Convergent Plate Margin of California - Wakabayashi, John (Frontiers in Earth Science, 2022)
Post-subduction dextral faulting was restored to evaluate the spatial distribution of units of the Franciscan subduction complex of California that formed as a result of subduction accretion. The Franciscan and related rocks of western California exhibit significant along-strike variation in its recording of subduction-accretion processes. Most notably, two segments 830 km apart record subduction erosion associated with low-angle subduction events that took place at ca. 120 Ma and ca. 80-70 Ma in the north and south, respectively. This spatial relationship is not affected by restoration of post-subduction dextral slip because none of the slip passes between the two inboard tectonic windows. Between these segments the subduction complex records net accretion from ca.175 Ma to 12 Ma, but includes horizons recording non-accretion. None of the accreted units of the subduction complex are preserved over the entire length of the subduction complex. One unit, however, correlated on the basis of its structural level in the subduction complex and distinctive detrital zircon age spectra, accreted at about 80-83 Ma extends a strike length of 580 km, an amount increased to 850 km with restoration of post-subduction dextral faulting. The long-strike length of accretion of this unit demonstrates that detrital zircon age populations of subduction complex clastic rocks are poor indicators of strike-slip displacement. Some reaches of the subduction complex include schistose blueschist facies rocks (most Franciscan blueschist facies rocks are not schistose), whereas others do not, and some reaches lack blueschist facies rocks altogether. The significant along-strike variation in the Franciscan and related rock units reflects temporal and spatial differences in history of accretion, non-accretion, subduction erosion, and probably subduction dip. Similar time and space variation in processes and resultant geologic record should be expected for other subduction complexes of the world.